An Overview of Self Maturity of Cheating Husbands: A Case Study - Nurul Indah Mustiyah; Siti Ina Savira (Character Jurnal Penelitian Psikologi, 2022)
Abstract The self-maturity of the husband is essential to creating a healthy and prosperous family. The absence of the husband's self-maturity can lead to infidelity which can affect the partner, family, and environment both physically and mentally. This study aims to provide an overview of the self-maturity of cheating husbands. The discussion uses a qualitative method with a case study approach. The informants of this study are five male informants who are married and have extramarital affairs. The data collection technique method uses semi-structured interviews, and the data is processed using thematic analysis to explore and find out the meaning that appears in the experience of the informants. The validity test of the data uses time triangulation to see the suitability of the finding of the study. The study finds the overview of self-maturity of cheating husbands generally tend to think irrationally, have difficulty controlling themselves, and lack close relationships with their wives. The internal and external factors contribute to the affairs of the five male informants.